Chlorinated biscoumarins inhibit chikungunya virus replication in cell-based and animal models - Chidinma Nelson Orji; Naphat Loeanurit; Van-Can Pham; Thi-Hong-Truc Phan; Kowit Hengphasatporn; Yasuteru Shigeta; Altri Diana Putri; Laura Sandra Lello; Andres Merits; Noppadol Wacharachaisurapol; Wanna Eiamart; Supeecha Wittayalertpanya; et al. (Emerging Microbes and Infections)
Biscoumarin derivatives were evaluated for antiviral activity against chikungunya virus (CHIKV), a re-emerging mosquito-borne alphavirus with no approved treatment. Compounds 3 and 4 demonstrated potent in vitro antiviral efficacy, with EC₅₀ values of 2.85 ± 0.42 µM and 3.08 ± 0.45 µM (SI > 20) for compound 3 in Vero and HEK293 cells, respectively. Compound 4 showed comparable potency in Vero cells but was less effective in HEK293 cells. Time-of-addition and replicon assays suggested that both compounds act at a post-entry step, likely inhibiting viral RNA replication. In vivo, a single oral dose of 250 mg/kg was well tolerated in mice and rats, with no signs of acute hepatorenal toxicity and favourable pharmacokinetic profiles. Compound 3 & 4 significantly reduced tissue viral loads within 24 hours; however, their antiviral effect diminished after the drug was cleared from circulation. Due to concerns about potential cumulative toxicity, repeated administration was avoided. Preliminary mechanistic studies indicated moderate inhibition of the viral nsP1 methyltransferase and suggested possible involvement of host pathways. These findings highlight biscoumarin derivatives – particularly compound 3 – as promising antiviral candidates against CHIKV, meriting further optimization and investigation into their mechanisms of action.